Raman response of topologically protected surface states in sub‐micrometric Pb0.77Sn0.23Se flakes. (28th September 2020) - Mehdipour, Sanaz; López‐Diaz, David; Velázquez, María Mercedes; Hidalgo, Pedro; Méndez, Bianchi; Luna, Mónica; Bellani, Vittorio; Amado, Mario; Balakrishnan, Geetha; Diez, Enrique
Abstract: The Raman spectra of the topological crystalline insulator Pb0.77 Sn0.23 Se flakes of thickness below 150 nm show the presence of plasma enhanced phonons related to topologically protected surface electronic states. The Fröhlich interaction between the topologically protected surface Dirac electrons and the phonons activates the forbidden phonons near the center of the Brillouin zone. An overtone is observed at a higher wavenumber, with a resonant response with temperature, related to an enhancement of the long‐range coupling between the topologically protected surface electrons and phonons. Abstract : The Raman spectra of the topological crystalline insulator Pb0.77 Sn0.23 Se flakes of thickness below 150 nm shows the presence of plasma enhanced phonons related to topologically protected surface electronic states. The Fröhlich interaction between the topologically protected surface Dirac electrons and the phonons activates the forbidden phonons near the center of the Brillouin zone.